Under a different sky - Savage, Deborah (New York : Penguin Putnam Books for Young Readers, 1998)
A boy with Olympic dreams and an extraordinary horse struggles to transcend his impoverished family background as he falls in love with the emotionally troubled daughter of a wealthy family.
"PaperStar.".
Books for the Teen Age (NYPL).
Publisher's Weekly.
School Library Journal starred.
Young Adult
Keywords: Boarding schools -- Fiction; Family problems -- Fiction; Horsemanship -- Fiction; Horses -- Fiction; Love -- Fiction; Schools -- Fiction; Family problems -- Fiction; Horsemanship -- Fiction; Horses -- Fiction; Love stories; Private schools -- Fiction; School stories